Altitudinal distribution and advertisement call of Colostethus latinasus (Amphibia: Dendrobatidae), endemic species from eastern Panama and type species of Colostethus , with a molecular assessment of similar sympatric species - Ibáñez, Roberto D.; Griffith, Edgardo J.; Lips, Karen R.; Crawford, Andrew J. (Zootaxa, 2017)
We conducted a molecular assessment of Colostethus-like frogs along an elevational gradient in the Serranía de Pirre, above Santa Cruz de Cana, eastern Panama, aiming to establish their species identity and to determine the altitudinal distribution of C. latinasus. Our findings confirm the view of C. latinasus as an endemic species restricted to the highlands of this mountain range, i.e., 1350–1475 m.a.s.l., considered to be type locality of this species. We described the advertisement call of C. latinasus that consists of a series of 4–18 single, short and relatively loud “peep”-like notes given in rapid succession, and its spectral and temporal features were compared with calls of congeneric species. For the first time, DNA sequences from C. latinasus were obtained, since previously reported sequences were based on misidentified specimens. This is particularly important because C. latinasus is the type species of Colostethus, a genus considered paraphyletic according to recent phylogenetic analyses based on molecular data.